2009
DOI: 10.1155/2009/904682
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Involved in Mesenchymal Stem Cell Migration to the Site of Acute Myocardial Infarction

Abstract: Mesenchymal stem cells or multipotent mesenchymal stromal cells (both referred to as MSC) have been shown in some studies to have a beneficial effect on myocardial recovery after infarct. Current strategies for MSC delivery to heart involve intravenous, intraarterial, and intramuscular delivery. Different routes of MSC delivery and a lack of knowledge of the mechanisms that MSC utilise to migrate in vivo has most likely led to the marked variations in results that have been found. This review aims to summarise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 84 publications
2
51
0
Order By: Relevance
“…68,69 Chemokines and chemoattractant signals also regulate the mobilization and homing of bone marrow-derived as well as circulating stem cell populations to the tissue repair sites, including MSCs and endothelial progenitor cells (EPCs). Under the guidance of chemokine signaling, MSCs can selectively migrate to injured sites, including skin wound healing, 63,70,71 bone fractures, 72,73 myocardial infarctions, 74,75 and ischemic cerebral injuries, 76 where they engraft and contribute to tissue recovery. 76 Interestingly, recent reports demonstrated that mechanical stretching can upregulate stromal cell-derived factor-1 alpha (SDF1a) and hypoxia-inducible factor-1 alpha in skin and recruit circulating MSCs and other stem cells through the SDF-1a/CXCR4 pathway.…”
Section: Chemokines In Fetal and Adult Wound Healingmentioning
confidence: 99%
“…68,69 Chemokines and chemoattractant signals also regulate the mobilization and homing of bone marrow-derived as well as circulating stem cell populations to the tissue repair sites, including MSCs and endothelial progenitor cells (EPCs). Under the guidance of chemokine signaling, MSCs can selectively migrate to injured sites, including skin wound healing, 63,70,71 bone fractures, 72,73 myocardial infarctions, 74,75 and ischemic cerebral injuries, 76 where they engraft and contribute to tissue recovery. 76 Interestingly, recent reports demonstrated that mechanical stretching can upregulate stromal cell-derived factor-1 alpha (SDF1a) and hypoxia-inducible factor-1 alpha in skin and recruit circulating MSCs and other stem cells through the SDF-1a/CXCR4 pathway.…”
Section: Chemokines In Fetal and Adult Wound Healingmentioning
confidence: 99%
“…tion, which was pronounced in L-MSCs compared with BMMSCs, is known to promote trans-endothelial migration and homing [54]. Also, L-MSCs expressed more PDGFRa, an important receptor for PDGF AA that regulates cell motility [55][56][57]. Similarly, directional migration as evidenced by chemo-attractant-driven responses to PDGF AA , PDGF BB , and FGF 2 in transwell experiments was also more pronounced in L-MSCs than BM-MSCs, consistent with differences in receptors (e.g., PDGFRa).…”
mentioning
confidence: 99%
“…However, some phenotypical specificities, such as higher expression of CD44 by PL-MSC, compared with MSCs from other dental tissues, could be due to the inflammatory origin of these cells (14). We found that STRO-1, a marker for MSCs (15), showed a lower membrane expression.…”
Section: Discussionmentioning
confidence: 64%